KONSTRUKSI MAKNA KREDIT SYARIAH BAGI KONSUMEN IBNU AUF DI KOTA PEKANBARU - Ranny Puspita Sari; Noor Efni Salam (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Shari’a credit as a phenomenon becomes an interesting study for research. Shari’a credit is a usury-free credit that has not yet existed in Pekanbaru City, considering that the credit system in Indonesian is still dominated by conventional credit containing usury. One of shari’a credit that exist in Pekanbaru City is Shari’a Credits Ibn Auf. The rise of Shari’a Credits Ibn Auf in Pekanbaru City affects consumers in interpreting shari’a credit. This study aims to determine how the Ibn Auf consumer’s motive in doing shari’a credit and how they interpret the shari’a credit they are living. This research uses qualitative methods with phenomenological approach. Subject of this research consists of ten consumers of Shari’a CreditsIbn Auf in Pekanbaru City, selected by purposive technique. Data collected byobservation, in-depth interviews, and documentation. To test the validity of the data the author uses an extension of participation and triangulation. The results of this research indicate the Ibn Auf consumer’s motivein doing shari’a credit consists of past motive (because motive) and future motive (in order to motive). Because motive of Ibn Auf consumer’s in doing shari’a credit are(1) chased by debt collector, (2) Discomfort in the household, (3) knowing about usury, (4) following sunnah study, and (5) join the usuryfree community. In order to motive Ibn Auf consumer’s in doing shari’a credit are(1) want to avoid sin, (2) preach, (3) enforce shari’a of Islam, (4) hijrah overall, (5) live peacefully, and (6) follow the trend of Islamic Economy. Ibn Auf consumer’s interpret the shari’a credit they are livingas (1) credit according to the shari’a, (2) da’wah media, (3) usury-free credit, and (4) credit solution for moslem.